Measuring progress from nationally determined contributions to mid-century strategies. Issue 12 (December 2017) - Iyer, Gokul; Ledna, Catherine; Clarke, Leon; Edmonds, James; McJeon, Haewon; Kyle, Page; Williams, James
Abstract The Paris Agreement requires countries to articulate near-term emissions reduction strategies through to 2025 or 2030 by communicating nationally determined contributions (NDCs), as well as encouraging the formulation of long-term low-emission development strategies (Article 4.19)1 . In response, many countries have either submitted or are preparing mid-century strategies2 . Most NDCs set high-level near-term goals—such as limits on emissions or emissions intensity3 —which do not provide information about the extent to which they lay the foundations of technology, infrastructure and institutions for deeper reductions in the future, which is a key question for decision makers. Here, using a state-level model of the US embedded within a global integrated assessment model4, 5, we demonstrate that although the US NDC lies on a straight-line emissions pathway towards its mid-century strategy, the resulting energy system transitions involve nonlinear transformations. The rates of capacity additions and capital investments in electricity generation beyond 2025 are more than three times the rates during the next decade. Our results demonstrate the need for global stocktaking exercises to evaluate the NDCs using metrics broader than emissions to better illuminate their effectiveness in addressing the Paris Agreement's long-term goals6, 7 . Achieving the longer-term goals of the Paris Agreement and transformation to a low-carbon society requires an acceleration in electricity generation investment and capacity addition above that outlined in the US Nationally Determined Contribution.